ANALISIS SEMIOTIKA JOHN FISKE DALAM KETIDAKSETARAAN GENDER PADA FILM DANGAL 2016 - Nova Yana Azli Harahap; Nursapia Harahap; Syahrul Abidin (Lafadz Jaya Publisher, 2023)
This study aims to find out how the representation gender inequality is represented and understand the meaning of the sign of the level of reality, representation, and gender ideology contained in the Dangal film. The theory which was used to explore this research is the theory of construction or injustice gender. The object of this research is the film Dangal 2016 which has a duration of 2 hours 41 minutes. The method used in this research is a qualitative method descriptive paradigm using John Fiske's semiotic analysis technique. Based on the results of the research studied by researchers in this film, they see meaning inferior which is described for women and superior meaning for men, this is illustrated in the struggle of two girls to keep living their lives even though their future is determined by the father. There are 13 scenes that show gender injustice in it. Delivery there is gender injustice in dangal films, namely by means of 3 levels the meaning of the sign, namely the Level of Reality, the Level of Representation and the Level of Ideology. So that in the end the meaning in this film is to change the opinion of society and defend the opinions and opinions of society against the values of patriarchal ideology.